Isolation and characterization of a flocculating protein from Moringa oleifera Lam - Gassenschmidt, Ursula; Jany, Klaus-Dieter; Tauscher, Bernhard; Niebergall, Heinz (Biochimica et biophysica acta. General subjects, 1995)
A flocculating protein from the seeds of Moringa oleifera Lam. was isolated by extraction with phosphate buffer followed by cation exchange chromatography. The molecular mass of the protein determined by SDS-PAGE was about 6.5 kDa, the isoelectric point was above pH 10. Amino acid analysis and sequencing showed high contents of glutamine, arginine and proline, and a total of 60 residues. The amino terminus is blocked by pyroglutamate. The flocculant capacity, determined in glass powder suspension, is comparable to that of a cationic polymer on polyacrylamide basis. Flocculation activity may be explained by the patch charge mechanism due to low molecular weight and high charge density.
Online verfügbar: 18. November 1999
Gesehen am 15.01.2026